AUDIT COMMITTEE AND INTERNAL AUDIT: IMPLICATIONS ON AUDIT QUALITY - Mat Yassin, Fatimah; Nelson, Sherliza Puat (International Journal of Economics, Management and Accounting, 2013)
The purpose of this study is to investigate the association of audit committee expertise and internal audit function characteristics, with audit quality, which is proxied by audit fee. As highlighted by prior studies, audit committee and internal audit are among the corporate governance mechanisms. Hence, among the corporate governance characteristics included in this study are audit committee expertise, frequency of audit committee meetings, structure of internal audit function and size of internal audit function. Using publicly available information, 200 Malaysian listed companies were utilised for both 2009 and 2010. It was shown that a positive relationship exists between external audit fee and two of the audit committee characteristics, i.e. audit committee with postgraduate qualification and frequency of audit committee meeting. Further, a positive relationship was found between external audit fee and a characteristic of the internal audit function, which is size of the internal audit function. Apart from contributing to the literature on corporate governance and audit quality, this study may serve as an input for regulators to encourage strict enforcement for Malaysian listed companies to incorporate corporate governance practices, especially in respect of audit committee composition and internal audit function. Finally, it highlights the call for continuous education for directors, to become more resourceful in order to improve their relationship with auditors.